MEDIA EFFECTS ON THE NEW YORK TIMES’ “THE WOMEN’S MARCH IN WASHINGTON” VIDEO NEWS COVERAGE ON FACEBOOK - AGRIPHINA, ALMIRA (LANTERN (Journal on English Language, Culture and Literature), 2017)
The reliance towards Facebook in regard to obtaining information becomes a news habit among the society. Considerable number of news coverage from media is accessible to Facebook which creates effects on the audience on account of the media exposure. The study is conducted for the purposes of analyzing news elements which are embedded in The New York Times’ “The Women’s March in Wahsington”video news coverage on Facebook and discovering the effects of the coverage towards media audience. This study is constructed as a library research which utilizes textual and user-response analysis research methodology. The theory utilizes to support the study is Pan &Kosicki’s Framing Analysis, and McComb& Shaw’s Agenda-Setting theory is also applied in this study to support the framing analysis. The results of the study indicate that three salient elements of the coverage set public agenda to which the salient elements become prominent issues of the Women’s March on Washington.